PENGGUNAAN MICROSOFT OFFICE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Arief Hidayat Afendi; Nurhidayati Sholihah; Fadzilatul Mutmainah; Khardianti Alviani Ishak; Adyanata Lubis (Jurnal PGSD, 2022)
ABSTRACT The world of education today began to integrate technology in various aspects including in learning. Education policy is directed to utilize information and communication technology on learning at least educators are able to master and teach to their students. Utilization of information and communication technology is able to increase the success of the teaching and learning process. The purpose and conduct of this learning is to increase motivation and understanding of students' learning outcomes in using microsoft office by utilizing information technology such as processing numbers, words, and simple animations. In microsoft office applications there are several applications in it such as microsoft word application, microsoft excel, microsoft power point which is to help students in the learning process by utilizing technology to increase motivation and understanding of student learning outcomes. Therefore, teachers can create learning methods with creative and innovative programs so that children are happy and motivated in learning starting from programs by words and numbers, learning to know colors, good at mathematics and have a lot of vocabulary in English. But in improving learning outcomes and student motivation, adequate facilities such as computers or leptop are needed to learn. Keywords: Microsoft Office, Motivation, Learning Outcomes, Elementary School Students. ABSTRAK Dunia pendidikan saat ini mulai mengintegrasikan teknologi pada berbagai aspek termasuk dalam pembelajaran. kebijakan pendidikan diarahkan untuk memanfaatkan teknologi informasi dan komunikasi pada pembelajaran setidaknya pendidik mampu menguasai dan mengajarkan kepada siswanya. Pemanfaatan teknologi informasi dan komunikasi mampu meningkatkan keberhasilan proses belajar mengajar. Tujuan dan dilakukannya pembelajaran ini untuk meningkatkan motivasi dan pemahaman terhadap hasil belajar siswa dalam menggunakan microsoft office dengan memanfaatkan teknologi informasi seperti mengolah angka, kata, dan animasi sederhana. Dalam aplikasi microsoft office terdapat beberapa aplikasi didalamnya seperti aplikasi microsoft word, microsoft excel, microsoft power point yang mana guna untuk membantu siswa dalam proses pembelajaran dengan memanfaatkan teknologi untuk meningkatkan motivasi dan pemahaman terhadap hasil belajar siswa. Maka dari itu guru dapat membuat metode pembelajaran dengan program yang kreatif dan inovatif sehingga anak senang dan termotivasi dalam belajar mulai dari program oleh kata dan angka, belajar mengenal warna, pandai dalam matematika dan memiliki banyak kosa kata dalam bahasa inggris. Namun dalam meningkatkan hasil belajar dan motivasi siswa dibutuhkannya fasilitas yang memadai seperti adanya komputer atau pun leptop untuk belajar. Kata kunci : Microsoft Office, Motivasi, Hasil Belajar, Siswa Sekolah Dasar.